Challenges of Teaching English Intonation Patterns to Uzbek-Speaking Students - Norpoʻlatova Nozima Yusufxon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the challenges of teaching English intonation patterns to Uzbek-speaking students. Intonation, an essential component of spoken English, affects meaning, emotion, and communication effectiveness. Uzbek learners often struggle with English intonation due to differences in stress patterns, sentence rhythm, and pitch variation between Uzbek and English. The study explores linguistic and pedagogical factors contributing to these difficulties and presents strategies for effective instruction. Techniques such as listening discrimination exercises, modeling, repetition, and communicative practice are emphasized. Classroom observations and research indicate that explicit instruction in intonation patterns enhances comprehension, pronunciation, and overall speaking confidence. The article also discusses pedagogical implications for EFL teachers in Uzbekistan and similar contexts.